Enabling Full-Duplex in a Wideband Indoor Base-Station Using Low-Complex Antenna Selection - Zarifeh, Nidal; Alissa, Mai; Kreul, Theo; Kaiser, Thomas (Loughborough Antennas & Propagation Conference 2018 (LAPC 2018), 2018)
This work proposes a practical method that combines wideband antenna selection and cross-polarization to enable full-duplex in an LTE femto base-station. A ray-tracing tool is used to characterize the indoor multi-path channel environment. Subsequently, a baseband analysis is done to evaluate the performance of the full-duplex system. Two antenna selection algorithms are tested: an optimal exhaustive method, and a practical low-complexity approach for real-case scenarios. It is shown that the high complexity, and the additional hardware, required for the optimal antenna-selection may be avoided without big drop in the performance of the full-duplex syst
Keywords: broadband antennas; ray tracing; transmitting antennas; antenna arrays; indoor radio; MIMO communication; femtocellular radio; multipath channels; Long Term Evolution; Mobile radio systems; Other topics in statistics; Optimisation techniques; Radio links and equipment; Single antennas